2003
DOI: 10.1159/000072563
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cerebral Blood Flow by Olprinone, a Phosphodiesterase-3 Inhibitor, in Mild Heart Failure

Abstract: Cerebral blood flow (CBF) is reduced in heart failure (HF). For the treatment of acute HF, a phosphodiesterase-3 inhibitor, olprinone (OL), yields an increase in myocardial contractility and a decrease in arterial afterload. During a 15-min intravenous infusion of OL (0.2 µg/kg/min), regional CBF at 6 sites of each cerebral cortex was examined using technetium-99m-ethylcysteinate dimer brain SPECT in 18 HF patients and 7 age-matched normal subjects. The baseline CBF was significantly reduced in HF (43.0 ± 3.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…28 In addition, it has been demonstrated that CBF is not affected by acute modulation of cardiac output. 2, 27 Similarly, we reported previously that CBF is associated with the serum B-type natriuretic peptide level and New York Heart Association functional class, which indicate the lateral cell columns of the spinal cord, which innervate the sympathetic neurons to the heart and kidney. 8, 9 Sympathetic excitations from these neural connections lead to left ventricular remodeling and dysfunction in the heart, vasoconstriction in the vascular tree, and sodium and fluid retention via renin release.…”
Section: Hf and Brain Functionmentioning
confidence: 52%
See 1 more Smart Citation
“…28 In addition, it has been demonstrated that CBF is not affected by acute modulation of cardiac output. 2, 27 Similarly, we reported previously that CBF is associated with the serum B-type natriuretic peptide level and New York Heart Association functional class, which indicate the lateral cell columns of the spinal cord, which innervate the sympathetic neurons to the heart and kidney. 8, 9 Sympathetic excitations from these neural connections lead to left ventricular remodeling and dysfunction in the heart, vasoconstriction in the vascular tree, and sodium and fluid retention via renin release.…”
Section: Hf and Brain Functionmentioning
confidence: 52%
“…3,23-26 In addition, previous study has reported that endogenous vasoactive molecules, such as intracellular adenosine monophosphate, led to cerebral vessel changes in HF patients. 27 However, we propose that these cerebral resistance vessels change as a result of a chronic adaptation to low cardiac output in advanced HF. A previous study showed that sustained alteration in cardiac output or systemic blood pressure can lead to structural changes in brain resistance vessels.…”
Section: Hf and Brain Functionmentioning
confidence: 91%
“…With a CBF difference of 5.0 ml/min/100 g between CHF patients and normal subjects, 40 samples for each group provided a power level of 98.0% with a type I error of 0.01 in the past study. 13 To examine whether CBF in the hippocampus is associated with depressive symptoms and memory impairment in CHF patients, we first applied univariate and multivariate regression analyses, and then CBF in the postero-posterior hippocampus was regressed onto confounding factors, echocardiography data and psychological test scores. For multivariate analysis, stepwise variable selection was used to identify the best subset of covariates associated with CBF in the postero-posterior hippocampus (multivariate analysis 1).…”
Section: Discussionmentioning
confidence: 99%
“…Amrinone and milrinone decrease infarct size in rabbit hearts with coronary artery branch occlusion via vasodilation to increase myocardial perfusion in the tissue surrounding the ischemic zone (Rump et al, 1994). Olprinone and cilostazol, both selective phosphodiesterase III inhibitors, are neuroprotective (Ueda et al, 2003;Ye et al, 2007), indicating that phosphodiesterase III may be broadly neuroprotective.…”
Section: Discussionmentioning
confidence: 99%